Edukacja polonistyczna w czasach populistycznej zarazy - Koc, Krzysztof (Paidia i Literatura, 2020)
The article encourages reflection on the role of Polish language education in the face of contemporary challenges. One of them is the expansion of populism (e.g. in politics, in the media, in the way of thinking about education) and the accompanying disinformation campaigns, propaganda or replacing information analysis with emotional opinions. We are also in Poland witnessing this disturbing process, which threatens the foundations of democracy. That is why teaching a critical attitude towards theses expressed in public discourse is so important. The article shows how access to reliable information can contribute to forming such an attitude. The author also suggests that the interpretation of modern children’s literature may be used to expose populist lies, harmful simplifications, and manipulation of facts; it can also successfully support the development of mature civic awareness even among very young students. The point of reference in this case is the problem of attitude towards refugees.